ALCOHOL-INDUCED LIVER INJURY: A RETROSPECTIVE STUDY EVALUATING LIVER FUNCTION TESTS IN A SOUTH AFRICAN POPULATION. - Mkhize, Nontokomalo; Thembane, Nokukhanya (Student’s Journal of Health Research Africa, 2023)
Background: Alcohol consumption is a major public health issue that has been linked to liver injury, which can be detected by liver function tests. However, limited research has been conducted on the effects of alcohol on liver function tests in African populations. Objectives: This retrospective observational study aimed to evaluate the effects of alcohol on liver function tests in a South African population. Materials and Methods: A total of 150 patients who had undergone liver function tests between May 2021 and December 2021 at a tertiary hospital in South Africa were included in the study. The mean values, t-tests, and p-values of liver function tests (TP, TB, ALT, AST, ALP, GGT, and Albumin) of male and female patients were analyzed. The De Ritis ratio was also calculated to assess the degree of liver injury induced by alcohol. Results: The results showed statistically significant differences in the mean values of the liver function tests between male and female patients. The De Ritis ratio was greater than 2 in 31% of the patients, indicating liver injury induced by alcohol consumption. Conclusions and Implications: The findings highlight the importance of regular monitoring of liver function tests in individuals who consume alcohol, particularly in African populations where limited research has been conducted on this topic. Further research is needed to explore the long-term effects of alcohol on liver function tests and to develop effective strategies for the prevention and treatment of alcohol-induced liver disease in African populations. The study provides insight into the effects of alcohol on liver function tests in South Africa and underscores the need for ongoing monitoring and prevention efforts to reduce the burden of alcohol-induced liver disease.